Exploring the oncoproteomic response of human prostate cancer to therapeutic radiation using data‐independent acquisition (DIA) mass spectrometry. Issue 8 (9th March 2018) - Keam, Simon P.; Gulati, Twishi; Gamell, Cristina; Caramia, Franco; Huang, Cheng; Schittenhelm, Ralf B.; Kleifeld, Oded; Neeson, Paul J.; Haupt, Ygal; Williams, Scott G.
Abstract : Introduction: The development of radioresistance in prostate cancer (PCa) is an important clinical issue and is still largely uninformed by personalized molecular characteristics. The aim of this study was to establish a platform that describes the early oncoproteomic response of human prostate tissue to radiation therapy (RT) using a prospective human tissue cohort. Methods: Fresh and fixed transperineal biopsies from eight men with clinically localized tumors were taken prior to and 14 days following a single fraction of high‐dose‐rate brachytherapy. Quantitative protein analysis was achieved using an optimized protein extraction pipeline and subsequent data‐independent acquisition mass spectroscopy (DIA‐MS). Ontology analyses were used to identify enriched functional pathways, with the candidates further interrogated in formalin‐fixed paraffin‐embedded tissue biopsies from five additional patients. Results: We obtained a mean coverage of 5660 proteins from fresh tissue biopsies; with the principal post‐radiation change observed being an increase in levels amongst a total of 49 proteins exhibiting abundance changes. Many of these changes in abundance varied between patients and, typically to prostate cancer tissue, exhibited a high level of heterogeneity. Ontological analysis revealed the enrichment of the protein activation cascades of three immunological pathways: humoral immune response, leukocyte mediated immunity and complement activation. These were predominantly associated with the extracellular space. We validated significant expression differences in between 20% and 61% of these candidates using the separate fixed‐tissue cohort and established their feasibility as an experimental tissue resource by acquiring quantitative data for a mean of 5152 proteins per patient. Discussion: In this prospective study, we have established a sensitive and reliable oncoproteomic pipeline for the analysis of both fresh and formalin‐fixed human PCa tissue. We identified multiple pathways known to be radiation‐responsive and have established a powerful database of candidates and pathways with no current association with RT. This information may be beneficial in the advancement of personalized therapies and potentially, predictive biomarkers.